Design and test of wireless monitoring system based on expandable awning composite greenhouse - Juhua Chen; Tingting Zhang; Xiaoyu Yan (Journal of Agricultural Engineering)
Wireless technologies like wireless fidelity (WIFI) and ZigBee have drawbacks such as short communication distances or high-power consumption, and the half-duplex nature of long range (LoRa) communication, traditional solutions generally use time division multiple access (TDMA) or polling communication methods，cannot provide differentiated services. Therefore, based on an extensible awning structure with fans and wet communication protocol combining TDMA and random delayed competitive access random delay competitive access (ALOHA) is proposed, which allows for real-time communication with contention nodes that have high real-time requirements, ensuring no data collisions during communication in static timeslot (TS) nodes, reducing node power consumption, and therefore achieved differentiated services. Practical verification demonstrates that the greenhouse achieves a 100% success rate in long-distance communication with low transmission power consumption. Although the competing node communication has data collision, the success of communication can be guaranteed by retransmission mechanism.